Reproductive Strategy of Chrysichthys nigrodigitatus (Lacepede, 1803) in a Natural Environment in the Nkam River, Littoral Cameroon - Tiogué, Claudine Tekounegning; Zebaze, Boddis Tsiguia; Zango, Paul; Tomedi-Tabi, Minette Eyango (International Journal of Zoology, 2020)
A study on the reproductive strategy of Chrysichthys nigrodigitatus was conducted from October 2015 to August 2016, in the Nkam River in Yabassi, Littoral Region of Cameroon. For this purpose, 154 specimens of C. nigrodigitatus with total mean weight of 829.96 ± 829.58 g and total mean length of 367 ± 156 mm collected from artisanal fishermen were used. Twenty-nine (29) females at stage V of sexual maturity were selected for the evaluation of the fecundity. It appears that the oogenesis in C. nigrodigitatus is of an asynchronous type with multiple laying spread over a long period. The gonadosomatic index (GSI) peaks in June (17.9 ± 7.1 for females and 1.06 ± 0.27 for males). Hepatosomatic index (HSI) was higher in females than in males throughout the year. The mean condition factor K was 1.07 ± 0.09%. The breeding season occurred from April to October during the rainy season. Gonadosomatic and hepatosomatic indices were positively correlated with rainfall, contrary to the K factor, which has been strongly and negatively correlated with this physical parameter. The sex ratio of 1M: 1.5F was in favour of females, thus reflecting an “r” type reproductive strategy. Absolute fecundity was estimated at 1374 ± 1022 oocytes for individuals of 107.3 ± 111.9 g mean weight. Mean relative fecundity was 14 ± 3 oocytes/g of body weight. It was recommended that future work focuses on the captivity of this species.